CFD modelling of post-combustion carbon capture with amine solutions in structured packing columns - Sebastia-Saez, J. Daniel (Cranfield University, 2016)
The scope of the present thesis is the development of a Computational Fluid Dynamics model to describe the multiphase flow inside a structured packing absorber for postcombustion carbon capture. The work focuses mainly on two flow characteristics: the interface tracking and the reactive mass transfer between the gas and the liquid. The interface tracking brings the possibility of studying the liquid maldistribution phenomenon, which strongly affects the mass transfer performance. The development of a user-defined function to account for the reactive mass transfer between phases constitutes the second major concept considered in this thesis. Numerical models found in the literature are divided into three scales due to the current computational capacity: small-, meso- and large-scale. Small-scale has usually dealt with interface tracking in 2D computational domains. Meso-scale has usually been considered to assess the dry pressure drop performance of the packing (considering only the gas phase). Large-scale studies the liquid distribution over the whole column assuming that the structured packing behaves as a porous medium. This thesis focuses on small- and meso-scale. The novelty of this work lies in expanding the capabilities of the aforementioned scales. At small-scale, the interfacial tracking is implemented in a 3D domain, instead of 2D. The user-defined function that describes the reactive mass transfer of CO2 into the aqueous MEA solution is also included to assess the influence of the liquid maldistribution on the mass transfer performance. At the meso-scale, the Volume of Fluid method for interface tracking is included (instead of only the gas phase) to describe flow characteristics such as the liquid hold-up, the interfacial area and the mass transfer. At the theoretical level, this model presents the particularity of including both a mass and a momentum source term in the conservation equations. A comprehensive mathematical development shows the influence of the mass source terms on the momentum equation.
Keywords: Carbon capture and storage; post-combustion; Structured packing; CFD; VOF; reactive mass transfer; multiphase flow; verification; validation